An Empirical Analysis of the Effects of Interest Rates and Exchange Rates on Stock Prices: Evidence from Astra International Plc - Gunawan, Hendri; Lisdawati, Lisdawati; Sulistyani, Tri (Indonesian Financial Review, 2025)
This study examines the effect of interest rates and exchange rates on stock prices of PT Astra International Tbk during the 2015–2024 period. Using a quantitative approach, the research applies multiple linear regression to secondary time-series data from Bank Indonesia and Investing.com. Classical assumption tests were conducted to ensure model reliability. The results show that interest rates do not have a significant partial effect on Astra’s stock price, while the exchange rate has a negative and significant influence. Simultaneously, interest rates and exchange rates do not significantly affect stock prices. The coefficient of determination indicates that 54.4 percent of stock price variation is explained by the two macroeconomic variables. These findings imply that exchange rate movements play a more important role than interest rates in shaping Astra’s stock performance and provide insights for investors in the Indonesian capital market.